Genetic patterns, host use and larval morphology in Tunisian populations of Orgyia trigotephras - Ezzine, Olfa; Hausmann, Axel; Branco, Manuela; Mannai, Yaussra; Dhahri, Samir; Nouira, Said; Ben Jamaa, Mohamed Lahbib (BULLETIN OF INSECTOLOGY, 2014)
Orgyia trigotephras Boisduval 1829 (Erebidae Lymantriinae) is a polyphagous moth widely distributed across the Mediterranean Basin. Current taxonomy validates several taxa at subspecies level within this species. Two of them, Orgyia trigotephras anceps Oberthur 1884 and Orgyia trigotephras transiens Staudinger et Rebel 1901 were found to occur in Tunisia. Although considered a rare species in southern Europe, an extensive outbreak was observed in Tunisia in the last decade. In this paper we present details on genetic patterns (mitochondrial DNA marker CO1), on larval phenotypic traits and on host plant species of Tunisian populations of O. trigotephras. Tunisian specimens clearly differentiated into two lineages, restricted to western and eastern Tunisia respectively. Both Tunisian haplotype-lineages strongly diverge from southern Spanish and southern Italian `conspecifics', questioning current taxonomy. Furthermore, we describe four larval phenotypes occurring in Tunisia and register Quercus coccifera, Quercus suber, Erica multiflora and Pistacia lentiscus as the four main host plant species. There was no association of the two genetic lineages with larval phenotypic traits. However, host plant species differed significantly between the two lineages.
The following values have no corresponding Zotero field: pub-location: DEPT AGROENVIRONMENTAL SCIENCES & TECHNOLOGY, VIALE G FANIN, 42, BOLOGNA, 40127, ITALY publisher: ALMA MATER STUDIORUM, UNIV BOLOGNA
Keywords: CO1; host plants; larval phenotypes; Orgyia trigotephras; phylogeography

Time to rethink the management intensity in a Mediterranean oak woodland: the response of insectivorous birds and leaf-chewing defoliators as key groups in the forest ecosystem - Pereira, Pedro; Godinho, Carlos; Roque, Inês; Marques, Ana; Branco, Manuela; Rabaça, João Eduardo (Annals of Forest Science, 2012)
Context The Iberian cork oak Quercus suber montados are dynamic agro-silvo-pastoral systems, contrasting with the abandonment trend of other Mediterranean forested areas. & Aims We aimed to identify the effect of management type and vegetation features on breeding insectivorous birds and leaf-chewing defoliator insects. & Methods In central Portugal, we selected two groups of 20 sites: dense montados (DM, high cover of cork oaks and low cattle impact) and sparse montados (SM, low cover of oaks and high cattle impact). We collected variables associated with vegetation features, bird community and chewing defoliators. & Results The two systems differed significantly in oak trunk diameter, oak and shrub cover, tree and shrub diversity. Ground bird densities were higher in SM with fragmented shrub cover. In DM, higher woody vegetation cover and diversity can promote shrub birds and leaf warblers. Oak defoliation was mainly attributed to the sawfly Periclista andrei. Sawfly defoliation was significantly higher in SM and negatively correlated with shrub cover. & Conclusions Our results highlight (1) the relevance of management activities conducted at the shrubby layer, (2) the need of an increase in tree diversity and density and (3) the maintenance of a mosaic landscape in order to improve the bird community richness and reduce the defoliation impact in montado system.
Keywords: birds; Cork oak; defoliators; management; mediterranean forest; montados

Establishing grazing and grazing-excluded patches increases plant and invertebrate diversity in a Mediterranean oak woodland - Bugalho, Miguel N; Lecomte, Xavier; Gonçalves, Merícia; Caldeira, Maria C; Branco, Manuela (Forest Ecology and Management, 2011)
Grazing is a global, dominant land use affecting biodiversity and ecosystem processes. In Mediterranean ecosystems grazing is a major ecological and evolutionary driver but, surprisingly, there is little information on the use of grazing as a tool to manage biodiversity in these ecosystems. We conducted an experiment to assess if establishing grazing and small scale grazing-excluded areas would increase plant and invertebrate diversity in a Mediterranean evergreen oak woodland. Plant community traits were different between treatments. Biomass of herbs (176.7±18.3 gm−2 vs 100.4±10.6 gm−2) and litter (291.0±38.3 gm−2 vs 186.8±26.4 gm−2), as well as the total cover of legumes (0.83±0.05 vs 0.91±0.03) were higher, and the proportion of bare ground (0.83±0.05 vs 0.91±0.03) was lower, in ungrazed plots. There were no differences in the number of plant species between treatments. Some plant species and invertebrate taxa were recorded exclusively in grazed or ungrazed plots. Invertebrate detritivores and sap sucking insects were more abundant in ungrazed plots. Ant assemblages were functionally different between treatments: Honeydew-gatherer ants were associated with ungrazed and higher plant biomass plots, and seed-eaters as well as aggressive predator ant species were associated with grazed, open habitat, plots. Management practices that maintain grazing and small scale grazing-excluded areas can increase habitat heterogeneity and promote herbaceous plant and invertebrate diversity at the local level.
Keywords: Cork oak; Deer; Grazing management; Holm oak; Land-use; montados

Germination success, survival and seedling vigour of Quercus suber acorns in relation to insect damage - Branco, Manuela; Branco, Carmen; Merouani, Hachemi; Almeida, Maria Helena (Forest Ecology and Management, 2002)
This study assesses the effects of damage caused by Curculio elephas Gyll. (Coleoptera: Curculionidae) and Cydia splendana Hb. (Lepidoptera: Tortricidae) on mature acorns of cork oak trees, Quercus suber L., in Portugal. The average number of insect-attacked acorns varied between 68, 44 and 17%, in three sites, respectively. Acorns assorted into increasing damage classes had a decreasing acorn dry weight and a faster germination rate. The percentage of germination was very high (>90%) in all classes. Seedlings resulting from more intensely damaged acorns exhibited a slower growth rate and lower dry mass production than seedlings resulting from low damaged acorns.
Keywords: acorn germination; insect-attack; seedling production

Germination success, survival and seedling vigour of Quercus suber acorns in relation to insect damage - Branco, Manuela; Branco, Carmen; Merouani, Hachemi; Almeida, Maria Helena (Forest Ecology and Management, 2002)
This study assesses the effects of damage caused by Curculio elephas Gyll. (Coleoptera: Curculionidae) and Cydia splendana Hb. (Lepidoptera: Tortricidae) on mature acorns of cork oak trees, Quercus suber L., in Portugal. The average number of insect-attacked acorns varied between 68, 44 and 17%, in three sites, respectively. Acorns assorted into increasing damage classes had a decreasing acorn dry weight and a faster germination rate. The percentage of germination was very high (>90%) in all classes. Seedlings resulting from more intensely damaged acorns exhibited a slower growth rate and lower dry mass production than seedlings resulting from low damaged acorns.
Keywords: acorn germination; insect-attack; seedling production